Mathematical modelling of the heterogeneity of disease progression and treatment outcomes in patients with COVID-19 - Yu, Guozhi; Huang, Houhui (Frontiers in Microbiology, 2025)
Pneumonia caused by SARS-CoV-2 infection is a self-limiting disease. Its progression and prognosis are highly heterogeneous among people of different ages, genders, and living with different life styles. Such heterogeneity also exists in treatment outcomes of different patients. Various physiological and pathological factors, such as renewal of pulmonary cell, number of entry receptor and viral replication, have been identified linking to the development of the disease. However, it is still unclear how these factors collectively establish a causal relationship in the course of disease progression. In this study, we built a mechanistic model to explain the dynamics of infection and progression of COVID-19. We modeled how the interaction of pulmonary cells determine the dynamics of disease progression by characterizing the temporal dynamics of viral load, infected and health alveolar cells, and dysfunctional alveolar cells. The viral and cellular dynamics captured different stages of clinical manifestations in individual patient during disease progression: the incubation period, mild symptom period, and severe period. We further simulated clinical interference at different stages of disease progression. The results showed that some medical interventions show no improvement either in reducing the recovery rate or shortening the recovery time. Our theoretical framework may provide a mechanistic explanation at the systems level for the progression and prognosis of COVID-19 as well as other similar respiratory tract diseases.